Analysis of Features and Classifiers in Emotion Recognition Systems: Case Study of Slavic Languages - Željko NEDELJKOVIĆ; Milana MILOŠEVIĆ; Željko ĐUROVIĆ (Archives of Acoustics)
Today’s human-computer interaction systems have a broad variety of applications in which automatic human emotion recognition is of great interest. Literature contains many different, more or less successful forms of these systems. This work emerged as an attempt to clarify which speech features are the most informative, which classification structure is the most convenient for this type of tasks, and the degree to which the results are influenced by database size, quality and cultural characteristic of a language. The research is presented as the case study on Slavic languages.